Mechanical and thermal properties of biocomposites from nonwoven industrial fique fiber mats with epoxy resin and linear low density polyethylene (2018)
In this work Linear Low Density Polyethylene-nonwoven industrial Fique fiber mat (LLDPE-Fique) andEpoxy Resin-nonwoven industrial Fique fiber mat (EP-Fique) biocomposites were prepared using thermo-compression and resin film infusion processes. Neat polymeric matrices and its biocomposites weretested following ASTM standards in order to evaluate tensile and flexural mechanical properties. Also,thermal behavior of these materials has been studied by differential scanning calorimetry (DSC) and ther-mogravimetric analysis (TGA). Tensile and flexural test revealed that nonwoven Fique reinforced com-posites exhibited higher modulus and strength but lower deformation capability as compared withLLDPE and EP neat matrices. TG thermograms showed that nonwoven Fique fibers incorporation hasan effect on the thermal stability of the composites. On the other hand, Fique fibers did not change thecrystallization and melting processes of the LLDPE matrix but restricts the motion of EP macromoleculeschains thus increases the Tg of the EP-Fique composite. Finally, this work opens the possibility of consid-ering non-woven Fique fibers as a reinforcement material with a high potential for the manufacture ofbiocomposites for automotive applications. In addition to the processing test specimens, it was also pos-sible to manufacture a part of LLDPE-Fique, and one part of EP-Fique